2013
DOI: 10.1111/cei.12186
|View full text |Cite
|
Sign up to set email alerts
|

Influenza infection results in local expansion of memory CD8+ T cells with antigen non-specific phenotype and function

Abstract: Summary Primary viral infections induce activation of CD8+ T cells responsible for effective resistance. We sought to characterize the nature of the CD8 + T cell expansion observed after primary viral infection with influenza. Infection of naive mice with different strains of influenza resulted in the rapid expansion of memory CD8 + T cells exhibiting a unique bystander phenotype with significant up-regulation of natural killer group 2D (NKG2D), but not CD25, on the CD44 high CD8+ T cells, suggesting an antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 70 publications
(120 reference statements)
3
59
0
Order By: Relevance
“…We and others have previously shown that these “bystander” activated CD8 + T cells perform their function in a more “NK-like” fashion using alternative receptors such as NKG2D for targeting transformed and virally infected cells rather than TCR mediated recognition (Chu et al, 2013; Sckisel et al, 2014; Tietze et al, 2011). Thus, the induction of bystander memory T activation, which is driven by cytokines and not antigen, necessitates the emergence of another control pathway which suppresses naïve CD4 + T cell expansion even with TCR triggering resulting in paralysis of primary T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that these “bystander” activated CD8 + T cells perform their function in a more “NK-like” fashion using alternative receptors such as NKG2D for targeting transformed and virally infected cells rather than TCR mediated recognition (Chu et al, 2013; Sckisel et al, 2014; Tietze et al, 2011). Thus, the induction of bystander memory T activation, which is driven by cytokines and not antigen, necessitates the emergence of another control pathway which suppresses naïve CD4 + T cell expansion even with TCR triggering resulting in paralysis of primary T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that they may be prime targets for immunomodulatory food products. While typically associated with adaptive immunity, memory T cells can also play an important role in innate immunity through antigen-independent, bystander effects [19, 20, 33, 34]. Therefore, they may be another innate-like lymphocyte population, in addition to γδ T cells and NK cells, whose numbers and activity could be influenced by polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…for 5 days, respectively) and recombinant human interleukin-2 (5 × 10^5 IU i.p. twice a week for 2 weeks) as previously described [18]. The anti-mouse CD40 antibody (clone FGK115B3) was generated via ascites production in our laboratory, as previously described [18].…”
Section: Methodsmentioning
confidence: 99%
“…twice a week for 2 weeks) as previously described [18]. The anti-mouse CD40 antibody (clone FGK115B3) was generated via ascites production in our laboratory, as previously described [18]. Recombinant human IL-2 (IL-2; TECIN Teceleukin) was provided by the National Cancer Institute repository (Frederick, MD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation